A non‐helical region in transmembrane helix 6 of hydrophobic amino acid transporter MhsT mediates substrate recognition. (6th November 2020) - Focht, Dorota; Neumann, Caroline; Lyons, Joseph; Eguskiza Bilbao, Ander; Blunck, Rickard; Malinauskaite, Lina; Schwarz, Ilona O; Javitch, Jonathan A; Quick, Matthias; Nissen, Poul
Abstract: MhsT of Bacillus halodurans is a transporter of hydrophobic amino acids and a homologue of the eukaryotic SLC6 family of Na + ‐dependent symporters for amino acids, neurotransmitters, osmolytes, or creatine. The broad range of transported amino acids by MhsT prompted the investigation of the substrate recognition mechanism. Here, we report six new substrate‐bound structures of MhsT, which, in conjunction with functional studies, reveal how the flexibility of a Gly‐Met‐Gly (GMG) motif in the unwound region of transmembrane segment 6 (TM6) is central for the recognition of substrates of different size by tailoring the binding site shape and volume. MhsT mutants, harboring substitutions within the unwound GMG loop and substrate binding pocket that mimick the binding sites of eukaryotic SLC6A18/B0AT3 and SLC6A19/B0AT1 transporters of neutral amino acids, exhibited impaired transport of aromatic amino acids that require a large binding site volume. Conservation of a general (G/A/C)ΦG motif among eukaryotic members of SLC6 family suggests a role for this loop in a common mechanism for substrate recognition and translocation by SLC6 transporters of broad substrate specificity. Synopsis: Bacillus halodurans MhsT transporter is the homologue of human SLC6 transporters and mediates uptake of a broad range of hydrophobic amino acids. Here, structural and functional data provide insight into the substrate recognition mechanism of MhsT with ramifications for SLC6 transporters and the larger family of LeuT‐fold proteins. Crystal structures of six MhsT/substrate complexes in the inward‐facing conformation reveal the role of the conserved unwound region of transmembrane segment (TM) 6 in substrate recognition, promiscuity and transport. The conserved (G/A/C)ΦG motif within the unwound part of TM6 is crucial for tailoring the volume of the central substrate site, thereby differentiating between branched aliphatic and larger aromatic amino acid substrates. The interaction between Glu66 located in TM2 and the unwound part of TM6 is conserved in all known conformational states and appears as a crucial mechanistic element of SLC6 transporters. Abstract : Structural and functional analyses of the Bacillus halodurans MhsT provide insight into sequence motifs underlying substrate recognition and their conservation in eukaryotic SLC6‐family Na + ‐dependent symporters.